2011
DOI: 10.2147/ijn.s25646
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of protein-entrapped liposomes and lipoparticles: preparation, characterization, and efficacy of cellular uptake

Abstract: Fluorescein isothiocyanate-conjugated bovine serum albumin (FITC-BSA)-loaded polyethylene glycol (PEG)-modified liposomes and lipoparticles with high protein entrapment were developed. The lipid formula of the liposomes contained PEGylated lipids and unsaturated fatty acids for enhancing membrane fluidity and effective delivery into cells. The preparation techniques, lipid content, and PEG-modified lipoparticle ratios were evaluated. The PEG-modified lipoparticles prepared by ethanol injection extrusion (100 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…Previous studies have further characterized SeNPs commonly used in our experiments. [15][16][17] Mammalian Cell Activity Culture and Characterization…”
Section: Senp Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have further characterized SeNPs commonly used in our experiments. [15][16][17] Mammalian Cell Activity Culture and Characterization…”
Section: Senp Characterizationmentioning
confidence: 99%
“…14 Researchers have shown that SeNPs may be used as a coating or directly in solution at dosages that reduce bacterial and cancerous growth while maintaining or promoting mammalian cell function. 9,[15][16][17][18][19] To fully utilize the potential of SeNPs, improved synthesis schemes are needed. Many SeNP schemes are multistep processes that involve the use of harsh solvents, such as benzene and toluene, 20 and/or strong bases, such as sodium hydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Therefore, new methods are needed, and green chemistry offers a suitable and novel answer, with the safe and environmentally friendly design, manufacturing, and use of chemical products that do not produce toxic and harsh by-products. 31,32 Green chemistry is considered an alternative approach in that it combines materials coming from synthetic chemistry and nature to overcome issues from traditional synthesis. Green chemistry approaches are especially useful for the generation of metallic nanoparticles (NPs), which have nanometric structures that effectively and efficiently address concerns in both health care and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…There has been no cell toxicity reported after administration of proteins encapsulated in conventional or sterically stabilized liposomes [43], [48], [49]. To assess the therapeutic index (TI) of our liposomes we tested for cytotoxicity over a wide dose range.…”
Section: Resultsmentioning
confidence: 99%